Use and forms of metadiscourse features in COVID-19 Malaysian news - Mei, Hooi Chee; Roy, Swagata Sinha; Md Ismail, Norhaniza Binti; Selvaraj, Thinusha A/P; Md Nor, Muhamad Elyas Bin; Affrin, Josephine Anak Freni; Darryl, Chow King; Woon, Tan Yee; Heng, Henry Tan Tze (Intelektual Pustaka Media Utama, 2025)
Metadiscourse features are fundamental for coherence and cohesion to be achieved by the writers in the texts. Writers might have employed metadiscourse widely, but they might have used it incorrectly, causing the texts to be disjointed. Numerous studies have been carried out in various academic contexts in the use of metadiscourse. However, there are still limited studies in news settings. Hence, the most common types, functions, and forms of metadiscourse features in coronavirus disease 2019 (COVID-19) news are identified through Dafouz-Milne’s model. Fifteen COVID-19 news articles were collected from The Star and The Edge, respectively from November 2021 to March 2022. The study is conducted to examine the comparison between textual and interpersonal functions and their forms. This is done to examine the engaging content in COVID-19 news from The Star or The Edge to create awareness for the journalists. The findings revealed that interpersonal metadiscourse was used more than textual metadiscourse for The Star, but textual metadiscourse was used more than interpersonal metadiscourse for The Edge. The findings also displayed the significance of metadiscourse in COVID-19 news, and a glossary of metadiscourse forms in COVID-19 news would expose the COVID-19 journalists and practitioners to the employment of metadiscourse.